Efeitos da prostaglandina E1 (PGE1) na gênese de capilares sanguíneos em músculo esquelético isquêmico de ratos obesos - Bueno, Fernanda Chagas (2012)
Several epidemiological studies show that obesity increases the risk of morbidity and mortality due to cardiovascular diseases. The number of patients with peripheral vascular diseases who can not be effectively treated with modern revascularization techniques has increased. As a consequence, severe ischemia, mainly on lower limbs develops, adversely affecting the quality of life for these patients. The angiogenic therapy is a promising technique that demonstrates that growth factors are able to increase capillary density. This technique is currently used to reduce the impact of ischemia in patients who have not had a satisfactory response to conventional treatments. Numerous substances have the ability to intensify the process of angiogenesis to compensate for tissue ischemia. Among the drugs used for this purpose is prostaglandin E1 (PGE1), a vasodilator that increases blood perfusion and improves peripheral endothelial function. Therefore, the aim of our study was to analyze the formation of new blood capillaries in skeletal muscle lower limb of obese rats, subjected to ischemia and/or the action of PGE1 administered intramuscularly. For this purpose, we used 57 Wistar rats were randomly divided into two groups, obesity and control, subsequently redistributed into two subgroups, ischemia (I) and ischemia with an intramuscular injection of PGE1 (I + PGE). Finally, the two groups were subdivided in 14 and 28 days of observation. To analyze the results, we used histological techniques with hematoxylin and eosin (HE) and immunohistochemistry. Anthropometric variables (body weight and adiposity) and lipid profile were analyzed. The results demonstrate a significant increase in the number of capillaries (PGE I + R 28 days 28 days 10.2 ± 2.0 vs. 7.2 ± 0.3 and 14 days PGE I + 9.3 ± 0.3 vs . I 14 days 5.5 ± 0.5) and capillary/muscle fiber ratio (1.70 ± 0.10 vs R + PGE. I 0.93 ± 0.06) in the obesity group with intramuscular injection of PGE1 at 28 days of observation. Immunohistochemistry using anti-VEGF-3 receptor were identified as positive markers of the reaction. Taken together, our data shows that angiogenic therapy induced an increase in the number of capillaries and consequent improve in blood flow in our experimental model, although in humans clinical trials should be carried out in order to demonstrate this effectiveness.